Gender and the performance of music - Sergeant, Desmond C.; Himonides, Evangelos (Frontiers in Psychology, 2014)
The study evaluates propositions that have appeared in the literature that music phenomena are gendered. If such propositions are substantive, gendered qualities might be imparted to the musical ‘message’ at any of three stages of the music–communication interchange: the process of composition, its realization into sound by the performer, or superimposed in the course of listener perceptions. Four research hypotheses are identified and relevant literature of music behaviours and perception reviewed. New instruments of measurement were constructed to test the four hypotheses: i) two listening sequences each containing 35 extracts from published recordings of compositions of the classical music repertoire, ii) four ‘music characteristics’ scales, with polarities defined by verbal descriptors designed to assess the dynamic and emotional valence of the musical extracts featured in the listening sequences. 69 musically trained listeners heard the two sequences and were asked to identify the sex of the performing artist of each musical extract; a second group of 23 listeners evaluated the extracts applying the four music characteristics scales. Results did not support claims that music structures are inherently gendered, nor proposals that performers impart their own-sex-specific qualities to the music. It is concluded that if gendering of music is a reality, the properties are imposed subjectively by the perceiver, and the respective qualities appear to be primarily related to the tempo of the music.